1987
DOI: 10.1037/0882-7974.2.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Ocular fixation control as a function of age and exposure duration.

Abstract: In previous work we reported that fixation stability did not deteriorate in older adults over relatively long viewing durations. In the present study we reanalyzed the data to examine potential aging effects on fixational control for viewing durations typically used in psychological experimentation. Monocular eye movements were recorded in 12 older and 12 younger observers using a dual Purkinje image technique, while observers fixated a stationary target. The two-dimensional scatter of eye positions was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…Contrary to older reports Kosnik et al 1987;Shallo-Hoffmann et al 1990), we observed greater oculomotor instability in the old adult group while fixating a target. Studies have shown that extra-retinal signals provide afferent and efferent input contributing to gaze direction information (Roll et al 1991), spatial orientation (Lewald and Ehrenstein 2000), the control of posture (Guerraz and Bronstein 2008;Kapoula and Lê 2006;Roll and Roll 1988;Strupp et al 2003;Wolsley et al 1996), and locomotion (Royden et al 1992).…”
Section: Age Effect On Frame Of Reference Selectioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Contrary to older reports Kosnik et al 1987;Shallo-Hoffmann et al 1990), we observed greater oculomotor instability in the old adult group while fixating a target. Studies have shown that extra-retinal signals provide afferent and efferent input contributing to gaze direction information (Roll et al 1991), spatial orientation (Lewald and Ehrenstein 2000), the control of posture (Guerraz and Bronstein 2008;Kapoula and Lê 2006;Roll and Roll 1988;Strupp et al 2003;Wolsley et al 1996), and locomotion (Royden et al 1992).…”
Section: Age Effect On Frame Of Reference Selectioncontrasting
confidence: 86%
“…Although it is known that oculomotor control is affected by age (Paige 1994;Pelak 2010), there is a discrepancy in the literature with regard to ageing on visual fixation stability. While some reports indicate greater instability with age (Hotson and Steinke 1988;Pelak 2010;Sekuler and Ball 1986), other studies have found no Kosnik et al 1987;Shallo-Hoffmann et al 1990) or limited (Herishanu and Sharpe 1981) age effects.…”
Section: Introductionmentioning
confidence: 92%
“…These studies use observational eye tracking, recording where young and older adults’ gaze fixates when either viewing faces or identifying emotional facial expressions. To the extent that gaze patterns lead to inaccuracy they may be considered “faulty”, though this not meant to imply any age-related change in the functioning of gaze patterns; in fact, research has shown age maintenance in fixational control (Kosnik, Kline, Fikre, & Sekuler, 1987). The idea that gaze patterns could lead to age-related inaccuracies in emotion recognition has been bolstered by research on emotion recognition among young individuals with autism; they have been found to show deficits in emotion recognition that can be linked to faulty gaze preferences, and may be improved by forced shifting of gaze onto more salient facial features (Neumann, Spezio, Piven, & Adolphs, 2006; Spezio, Adolphs, Hurley, & Piven, 2007).…”
Section: Age Differences In Mechanismsmentioning
confidence: 99%
“…The retinal locus for fixation in normally-sighted subjects remains within 160 arcmin 2 1 corresponding to a retinal diameter of approximately 35 foveal cone cells. Macular diseases, including age-related macular degeneration (AMD), may damage the fovea through various pathologic processes resulting in a discrete region of blindness called a scotoma.…”
mentioning
confidence: 99%